Comparison of OSCE Scores of Surgical Clinical Education after Face-to-face vs. Blended Learning Methods among undergraduate medical students - Masood Jawaid; Lubna Baig; Syed Moyn Aly (Journal of the Pakistan Medical Association, 2021)
Objective: Clinical education is an important component of undergraduate medical education. This study compares the efficacy of blended learning (BL) with contemporary face to face (F2F) teaching among medical students by assessing their OSCE scores at end of clinical posting. Methods: This experimental study was conducted in Dow University of Health Sciences from March to August 2014. Third-year medical students posted in the surgical units were divided into two groups. In the first month, one group in the unit was taught by BL while the second group posted in another unit was taught by F2F teaching. Both groups were assessed by same OSCE. In the second month, teaching method was flipped for both the groups with new learning contents. assessment was by the same OSCE for both groups. Data was analyzed by SPSS version 23 with inferential statistics with independent sample t test. Results: A total of 28 students were assessed at the end of posting OSCE in F2F group and 31 students in blended group. There was significant difference in OSCE score [p value = 0.049] after F2F teaching method (78.01 ± 13.29) as compared to BL (85.12 ± 13.77). The domain of “log book” and “clinical examination” scored higher in F2F as compared to BL group. Conclusion: This study showed that student performance can be improved with a blended surgical learning program. BL has proven to be more effective in comparison to face-to-face teaching alone, even in the setting of skill based curriculum like surgery.